Akibat Hukum Wanprestasi Dalam Perjanjian Sewa Menyewa Menurut Kitab Undang-Undang Hukum Perdata - Anak Agung Dewi Utari; Yusika Riendy; Edi Sofwan (Amal Insani Foundation, 2022)
A lease is an agreement whereby one party binds himself to give the other party the enjoyment of an item for a certain period and with payment of a price that the latter party is willing to pay. The rights and obligations of the parties in the lease agreement and the rights of the lessor are the rights that the lessor will receive. The party who rents out has the right to pandbeslag, which is a confiscation carried out by the court at the request of the renter, such as the furniture in the house that is being rented if the tenant is in arrears with the rent for the house to be auctioned if the tenant does not pay off the arrears. The lessor has the right to request cancellation of the agreement and compensation. The lessor's right is to hand over the leased to the lessee to maintain the object being leased so that the object can be used for its intended purpose. The lease agreement ends in default before the expiration of the agreement, i.e., the lease agreement can terminate automatically at a particular time after being terminated by taking into account a certain grace period. Although a lease is a consensual agreement, by law, there is a difference between a written lease and an oral lease.